The Influence of digital marketing on purchase decisions of florist products: the mediating role of brand awareness and customer trust - Lamanepa, Amelia Wulandari; Hermeindito, Hermeindito (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2025)
The increasing penetration of the internet in Indonesia, which reached 79.5% in 2024, has significantly influenced the dynamics of business and consumer interaction, particularly in the digital marketplace. Despite these advancements, specific sectors, such as the florist industry, have not fully capitalized on digital opportunities. This study aims to address a research gap concerning the effectiveness of digital marketing strategies within the florist sector by examining the case of Auriel Florist Surabaya, a business experiencing a decline in sales despite active online promotional efforts. Employing a quantitative research design, data were collected through a survey of 100 customers and analyzed using SmartPLS to examine the relationships among digital marketing, brand awareness, customer trust, and purchase decisions. The results indicate that digital marketing has a significant positive impact on brand awareness, which in turn has a strong influence on purchase decisions. In contrast, customer trust does not exhibit a direct significant impact on purchase decisions. These findings suggest that brand recognition plays a more critical role in shaping consumer behavior than trust alone. Future studies are recommended to incorporate additional variables and test the model across different industries to enhance generalizability.